2022
DOI: 10.1158/1535-7163.mct-21-0836
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Surfaceome Profiling to Identify and Validate Novel Cell-Surface Targets in Osteosarcoma

Abstract: Immunoconjugates targeting cell-surface antigens have demonstrated clinical activity to enable regulatory approval in several solid and hematologic malignancies. We hypothesize that a rigorous and comprehensive surfaceome profiling approach to identify osteosarcoma-specific cell-surface antigens can similarly enable development of effective therapeutics in this disease. Herein, we describe an integrated proteomic and transcriptomic surfaceome profiling approach to identify cell-surface proteins that are highly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Our study showed that B7-H3 was obviously overexpressed on tumor cell membrane among all the other immune checkpoint molecules as a member of the B7 ligand family, which was also in accordance with the recent publication by Wang et al, 27 who used an integrated proteomic and transcriptomic surfaceome profiling approach to identify cellsurface proteins that are highly expressed in osteosarcoma. Nguyen et al 28 and Wang et al 29 had also tried to identify the positive rate and intensity of B7-H3 for osteosarcoma patients and found it as an attractive target, which encouraged Kendsersky et al 30 to do B7-H3-targeting antibodydrug conjugates against preclinical osteosarcoma models with significant anti-tumor activity.…”
Section: B7-h3 For Osteosarcomasupporting
confidence: 92%
“…Our study showed that B7-H3 was obviously overexpressed on tumor cell membrane among all the other immune checkpoint molecules as a member of the B7 ligand family, which was also in accordance with the recent publication by Wang et al, 27 who used an integrated proteomic and transcriptomic surfaceome profiling approach to identify cellsurface proteins that are highly expressed in osteosarcoma. Nguyen et al 28 and Wang et al 29 had also tried to identify the positive rate and intensity of B7-H3 for osteosarcoma patients and found it as an attractive target, which encouraged Kendsersky et al 30 to do B7-H3-targeting antibodydrug conjugates against preclinical osteosarcoma models with significant anti-tumor activity.…”
Section: B7-h3 For Osteosarcomasupporting
confidence: 92%
“…However, the efficacy of immunotherapy remains uncertain and is less effective for high‐risk, recurrent, and metastatic patients 14 . Additionally, research on targeted drug delivery using nanocarriers shows promise, but the specific tumor microenvironment and unclear targets pose challenges, hindering the use of emerging targeted therapies in OS treatment 15,16 . Therefore, while conventional treatment methods have some effectiveness in treating OS, their inherent limitations necessitate the urgent development of alternative treatment approaches to overcome these limitations.…”
Section: Conventional Treatment For Osmentioning
confidence: 99%
“…317,318 It is also generated in healthy tissues but is overexpressed in various tumor types, including osteosarcoma, and high CD276 expression is closely related to increased quantities of Tregs across tumor tissues, suggesting that CD276 has a positive effect on Treg-mediated suppression of T lymphocyte function. [319][320][321][322] In a lymphoma mouse model, Lee et al found that blocking the immune checkpoint CD276 effectively inhibited tumor progression, and combination of this strategy with an anti-PD-1 antibody led to further improved therapeutic efficacy in advanced tumors. 318 Additionally, several preclinical reports have also shown the potential of using CAR-T lymphocytes or microRNAs (such as miR-124) to target B7-H3 to improve osteosarcoma immunotherapy.…”
Section: Immune Checkpoint Blockade-based Immunotherapy For Osteosarcomamentioning
confidence: 99%